Evaluation of Femoral Nerve Blockade for Postoperative Analgesia in Dogs Undergoing Stifle Arthrotomy - Cox, K. R.; Riedesel, D. (Veterinary and Comparative Orthopaedics and Traumatology, 1997)
The efficacy of the femoral nerve block (FNB) in alleviating postoperative pain was evaluated in dogs undergoing stifle arthrotomy. The pre- and postoperative nerve blocks were compared to intraarticular administration of a local anaesthetic. Forty-eight dogs with a ruptured cranial cruciate ligament were randomly assigned to the following groups: Group A (n = 16) received a femoral perineural injection prior to surgery; eight dogs within this group were given 0.5% bupivacaine and eight dogs received 0.9% saline. Group B (n = 16) had a femoral perineural injection immediately after surgery; eight dogs received 0.5% bupivacaine and eight received 0.9% saline. Group C (n = 16) dogs were given 0.5% bupivacaine (n = 8) or 0.9% saline (n = 8) intraarticularly. Postoperative pain was evaluated using a visual analog scale and a numerical rating scale, including measurement of heart rate, respiratory rate and systolic pressure. The dogs were scored preoperatively and at zero to six and at 24 hours after the operation. A significant difference was not noted between groups during the time until the first dose of supplemental analgesia nor in the total dose of supplemental analgesia required. The duration of the operation was found to be negatively correlated with the duration of postoperative analgesic effect. There was not any significant difference between the groups in pain scores at any time.Femoral nerve block (FNB) was evaluated for the control of postoperative pain in dogs undergoing stifle arthrotomy. FNB, using bupivacaine, was performed preoperatively and was compared to a postoperative FNB, and to saline controls. In addition, the efficacy of the FNB was compared to intra-articularly administered bupivacaine. Differences were not found between any groups in the alleviation of postoperative pain.
Keywords: Canine; femoral nerve block; bupivacaine; postoperative analgesia; preemptive analgesia